Fracture analysis of Ag nanobrazing of NITi to Ti alloy - Quintino, Luísa (2018)
LQ and RM acknowledge funding from the Portuguese Science and Technology Foundation for the project "MICRO-BOND" (PTDC/EME-TME/100990/2008). RM acknowledges Pest OE/EME/UI0667/2011.